SOME FEATURES OF LANGUAGE IN THE BLIND CHILD - Pérez Pereira, Miguel (Anales de Psicología / Annals of Psychology)
The view on language acquisition in the blind child that shows a delay and some features that make it deficient is criticized. The language of a blind born girl is compared with that of her twin sighted sister. The analysis suggests that: (1) the language development of the blind infant can not be considered delayed as it displays a higher MLU than that of her sister; (2) her language is not odd nor limited as for the functions it serves, and it seems appropriated for her adaptation to the world; (3) the blind girl shows an ability to analyze the morphology of language and the use of rules because both infants make similar overregularization mistakes; (4) the use and quality of imitations, repetitions and routines by the blind girl is both an index of an strategy and an instrument for analyzing the language in the acquisition process; (5) the nature of imitations, repetitions and routines is progressive, as they are used in more complex grammatically sentences than the whole of utterances. It is concluded that the blind infant's language is not defective nor delayed in relation to that of her sister. Moreover, the blind girl shows a gestaltist style in language processing.